A Case of Ullrich-Turner Syndrome with 45,X/46,XY Karyotype - Yüce, Hüseyin; Akın, Haluk; Etem, Ebru; Deveci, Şükriye Derya (Fırat University, 2004)
The presence of mosaic 45,X/46,XY is a very rare chromosomal anomaly, with an incidence of about 1.5 per 10.000 in newborn infants and in midtrimester amniocentesis. The phenotype can vary from a normal male to a classical Ullrich-Turner syndrome (UTS). This patients are often infertile. The proposita presented at short stature, primary amenorrhea and hypoplasic uterus. Clinical examination revealed multiple Turner syndrome stigmata. Proposita karyotype was determined as 45,X/46,XY by cytogenetic analysis of peripheral blood. Fluorescence in situ hybridization (FISH) method was performed using centromeric X and Y probe to define the exact mosaicism rate. The rate of mosaicism is found as 45,X(%27)/46,XY(%73) by molecular cytogenetic evaluation. Sex determination was performed using pesudoautosomal region specific primers to establish definitely presence of Y chromosome. In this detection, the case revealed specific bands for Y and X chromosomes. It is impotant to determine definitely mosaicism rate, presence of Y chromosome and sex in UTS patients in terms of prognosis of the disease. It has been presented the importance of the presence Y chromosome in patients with UTS and genetic counseling process labaratory findings in this relatively rare seen case by discussing in view of the literature. ©2004, Fırat Üniversitesi, Tıp Fakültesi

45,X/46,XY mozaikliği nadir görülen kromozomal bir anomalidir. Her 10.000 yeni doğan bebekte ve ikinci trimester amniyosentezlerinde yaklaşık 15 oranında görülmektedir. Oluşan fenotip normal bir erkekten klasik Ullrich-Turner Sendromuna (UTS) kadar değişmektedir. Bu bireyler sıklıkla infertildir. Olgu kısa boy, primer amenore ve hipoplazik uterus göstermekteydi. Klinik muayene sonucunda bir çok Turner sendromu bulguları ortaya kondu. Probandın karyotipi, periferik kandan yapılan sitogenetik inceleme sonucu, 45,X/46,XY olarak saptandı. Mozaiklik oranının tam olarak belirlenmesi için sentromerik X ve Y probları kullanılarak Fluoresans in situ Hibridizasyon (FISH) yöntemi uygulandı. Mozaiklik oranı moleküler sitogenetik inceleme sonucu 45,X(%27)/46,XY(%73) olarak bulundu Y kromozomunun kesin varlığının ortaya konması için pseudootozomal bölgeye spesifik primerler kullanılarak cinsiyet tayini gerçekleştirildi. Bu incelemede, olgu X ve Y krom zomları için özgül bantlar gösterdi. UTS hastalarında bireyin cinsiyetinin, mozaiklik oranının ve Y kromozomuna ait dizilerin varlığının kesin olarak ortaya konması, hastalığın prognozunun belirlenmesi açısından oldukça önemlidir. UTS olgularında Y kromozom varlığının önemi ve nispeten nadir olarak görülen bu olguda laboratuar bulguları ile birlikte genetik danışmanlık süreci literatür ışığında tartışılarak sunulmuştur. ©2004, Fırat Üniversitesi, Tıp Fakültesi
45,X/46,XY Karyotipine Sahip Ullrich-Turner Sendromlu Bir Olgu